Clearance of replicating hepatitis C virus replicon RNAs in cell culture by small interfering RNAs - Randall, Glenn (The National Academy of Sciences, 2003)
RNA interference is a cellular process of gene silencing in which small duplexes of RNA specifically target a homologous sequence for cleavage by cellular ribonucleases. The introduction of ≈22-nt small interfering RNAs (siRNAs) into mammalian cells can specifically silence cellular mRNAs without induction of the nonspecific IFN responses that are activated by longer RNA duplexes. We investigate in this article whether siRNAs can also silence the expression of the cytoplasmically replicating hepatitis C virus (HCV) RNAs by using a replicon system that supports robust HCV replication, but not the production of infectious virions. We report the efficient silencing of both cellular lamin A/C and HCV RNAs in Huh-7 hepatoma cell lines supporting HCV replication. Silencing of HCV RNAs was dose dependent and specific, inasmuch as two HCV variants that differ by 3 nt within the target sequence were only silenced by the exact homologous sequence for each. siRNAs designed to target HCV RNA triggered an exponential decrease in HCV RNA, resulting in an 80-fold decrease in HCV RNA after 4 days. The introduction of siRNAs into cells with established HCV replication cured >98% of these cells of detectable HCV antigen and replication-competent HCV RNAs. These data support the principle of siRNA-based HCV antiviral therapy.